Dissemination of Evidence From Systematic Reviews Through Academic CME Providers: A Feasibility Study. Issue 2 (2016) - Fordis, Michael; King, Jason E.; Bonaduce de Nigris, Francesca; Morrow, Robert; Baron, Robert B.; Kues, John R.; Norton, James C.; Kessler, Harold; Mazmanian, Paul E.; Colburn, Lois
Abstract : Introduction: Although systematic reviews represent a source of best evidence to support clinical decision-making, reviews are underutilized by clinicians. Barriers include lack of awareness, familiarity, and access. Efforts to promote utilization have focused on reaching practicing clinicians, leaving unexplored the roles of continuing medical education (CME) directors and faculty in promoting systematic review use. This study explored the feasibility of working with CME directors and faculty for that purpose. Methods: A convenience sample of five academic CME directors and faculty agreed to participate in a feasibility study exploring use in CME courses of systematic reviews from the Agency for Healthcare Research and Quality (AHRQ-SRs). AHRQ-SR topics addressed the comparative effectiveness of health care options. Participants received access to AHRQ-SR reports, associated summary products, and instructional resources. The feasibility study used mixed methods to assess 1) implementation of courses incorporating SR evidence, 2) identification of facilitators and barriers to integration, and 3) acceptability to CME directors, faculty, and learners. Results: Faculty implemented 14 CME courses of varying formats serving 1700 learners in urban, suburban, and rural settings. Facilitators included credibility, conciseness of messages, and availability of supporting materials; potential barriers included faculty unfamiliarity with SRs, challenges in maintaining review currency, and review scope. SR evidence and summary products proved acceptable to CME directors, course faculty, and learners by multiple measures. Discussion: This study demonstrates the feasibility of approaches to use AHRQ-SRs in CME courses/programming. Further research is needed to demonstrate generalizability to other types of CME providers and other systemic reviews.